Recent advances in nano-drug delivery systems for synergistic antitumor immunotherapy - Zhao, Bonan; Li, Xiang; Kong, Ying; Wang, Wenbo; Wen, Tingting; Zhang, Yanru; Deng, Zhiyong; Chen, Yafang; Zheng, Xian (Frontiers in Bioengineering and Biotechnology, 2022)
Immunotherapy has demonstrated great clinical success in the field of oncology in comparison with conventional cancer therapy. However, cancer immunotherapy still encounters major challenges that limit its efficacy against different types of cancers and often the patients show minimal immune response to the immunotherapy. To overcome these limitations, combinatorial approaches with other therapeutics have been applied in the clinic. Simultaneously, nano-drug delivery system has played an important role in increasing the antitumor efficacy of various treatments and has been increasingly utilized for synergistic immunotherapy to further enhance the immunogenicity of the tumors. Specifically, they can promote the infiltration of immune cells within the tumors and create an environment that is more sensitive to immunotherapy, particularly in solid tumors, by accelerating tumor accumulation and permeability. Herein, this progress report provides a brief overview of the development of nano-drug delivery systems, classification of combinatory cancer immunotherapy and recent progress in tumor immune synergistic therapy in the application of nano-drug delivery systems.